2016
DOI: 10.1126/sciadv.1600377
|View full text |Cite
|
Sign up to set email alerts
|

The new world atlas of artificial night sky brightness

Abstract: The world atlas of zenith artificial night sky brightness is modelled with VIIRS DNB data and calibrated with more than 35,000 observations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
931
2
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,136 publications
(1,052 citation statements)
references
References 38 publications
13
931
2
17
Order By: Relevance
“…In some cases, we found that terms focused mostly on what citizen scientists were not, e.g., non-credentialed, Falchi et al (2016) found that the data from "scientists known to us" (i.e., professionals, but including specifically recruited amateur astronomers) had a greater variance, bias, and number of outliers than data from "scientists unknown to us" (i.e., citizen scientists, but likely including many professional scientist contributors). We also found some terms that tended to be used for more general audiences, including ' amateur,' 'hobbyist,' 'volunteer,' 'layperson,' and 'general public.'…”
Section: 'Citizens'mentioning
confidence: 96%
“…In some cases, we found that terms focused mostly on what citizen scientists were not, e.g., non-credentialed, Falchi et al (2016) found that the data from "scientists known to us" (i.e., professionals, but including specifically recruited amateur astronomers) had a greater variance, bias, and number of outliers than data from "scientists unknown to us" (i.e., citizen scientists, but likely including many professional scientist contributors). We also found some terms that tended to be used for more general audiences, including ' amateur,' 'hobbyist,' 'volunteer,' 'layperson,' and 'general public.'…”
Section: 'Citizens'mentioning
confidence: 96%
“…Global satellite-observed night-time lights have emerged as one of the widely used geospatial data products (Amaral et al 2005;Small, Pozzi, and Elvidge 2005;Sutton et al 2007;Bharti et al 2009;Chand et al 2009;Ghosh et al 2010;Oda and Maksyutov 2011;Witmer and O'loughlin 2011;He et al 2012;Mazor et al 2013;Min et al 2013;Falchi et al 2016). These products show the locations where artificial lighting is present and a measure of the brightness as observed from space.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of moonlight depends on several factors, like the Moon phase, the EarthMoon distance, the altitude of the Moon over the horizon, and the local atmospheric conditions, including the aerosol concentration profile, the optical density of the atmosphere, and the type, structure, fraction of sky coverage and optical properties of clouds, among other. Typical estimates set at about E m =0.27 lx the maximum moonlight illuminance at ground level (Driggers et al, 2012 Artificial skyglow (Cinzano et al, 2001;Falchi et al, 2016) is an additional brightness source contributing to the urban spectral radiance, apart from the direct artificial lights and moonlight. Our field measurements include the effects of this additional source.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial skyglow in clear and moonless nights in widely populated urban areas may easily reach zenithal values in excess of L s =7.3x10 −3 cd/m 2 (Falchi et al, 2016 Note however that, from a radiometric viewpoint, there are two factors that contribute to enlarge the effective photoreceptoral field. One of them is the presence in all physiologically normal eyes of several kind of optical aberrations that contribute to enlarge the eye's optical point spread function to typical sizes of order several minutes of arc (Navarro et al, 1998).…”
Section: Discussionmentioning
confidence: 99%